Relationships among Non-English Majors’ EFL Listening Practice Time, Listening Proficiency, and Proficiency Change - Lee, Hui-Ming Lucy (Widya Mandala Catholic University Surabaya, 2017)
This study aimed to explore the amount of time EFL learners spent practicing listening and to assess the relationships among time, proficiency, and proficiency change. The participants consisted of 142 Taiwanese non-English majors. For 15 weeks, a daily time log was used as the instrument to measure the time spent listening. The results revealed that most students spent little time on listening materials. There were significant proficiency changes for the whole sample and the three proficiency levels. In regards to the whole sample, the total time spent on all materials did not significantly correlate with either proficiency or growth. However, significant relationships were found among time, proficiency, and gains in terms of the types of materials and proficiency levels. The daily time log with a larger sample size is recommended for further studies for a clearer understanding of the role of practice time in EFL listening acquisition.